THE ELECTRONIC SERVICE QUALITY STRUCTURAL EQUATION MODEL FOR CUSTOMER SATISFACTION AND LOYALTY IN ONLINE FOOD PURCHASES THROUGH GRAB FOOD APPLICATION IN THAILAND - Vuthisopon, Sujira (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The objective of this study was to study the influence of electronic service quality on Customer satisfaction and loyalty in online food purchases through the Grab Food application, as well as developing and validating a model of structural equations developed with empirical data consisting of key latent variables. 3 variables: quality of electronic services Customer satisfaction and customer loyalty in online food purchases through Grab Food using quantitative research methods, empirical research and questionnaires were used as a tool to collect information from customers who used the service. 260 people were shopping online through Grab Food. The statistics used for data analysis were descriptive statistics. One-way analysis of variance and analysis of structural equation models from the research results it was found that The e-service quality structural equation model on customer satisfaction and loyalty in online food purchases through Grab Food was consistent with empirical data. The chi-square is 784.25 at the degrees of freedom (df) 395, the probability (p-value) is 0.485, the relative chi-square (X2 / df) is 2.879, the degree of harmony index (GFI) is 0.796 value. The parameter RMSEA is 0.025, with electronic service quality having both direct and indirect positive influences on customer loyalty. And customer satisfaction has a direct positive influence on loyalty. The samples with different frequency of purchasing food online through Grab Food had statistically different levels of electronic service quality.